An uncommon manifestation of mixed connective tissue disorder presenting as dilated cardiomyopathy - Ashok Jain (Heart India, 2025)
Mixed connective tissue disorder is a systemic autoimmune disorder that can affect any organ in the system including the heart. Varied cardiac manifestation of mixed connective tissue disease has been reported including pericarditis, pulmonary hypertension, and myocarditis. The patient presenting as dilated cardiomyopathy (DCM) in mixed connective tissue disorder is rarely been reported. The need of search for the cause of DCM is essential in every case of DCM, as in our case lead to the diagnosis of mixed connective tissue disorder. A coronary angiogram of the same patient has shown myocardial bridging association of which needs further study.